Stratified Prognostic Value of Pathological Response to Preoperative Treatment in yp II/III Rectal Cancer - Yang, Yanpeng; Xu, Hao; Chen, Guowei; Pan, Yisheng (Frontiers in Oncology, 2021)
Aim: Accumulated studies have verified that tumor regression is associated with the prognosis of rectal cancer. However, stratified analysis within a certain stage is still unknown. The purpose of our study was to assess the impact of pathologic response on the survival of stageII and III rectal cancer patients after neoadjuvant chemoradiotherapy (nCRT). Methods: Clinicopathologic characteristics and tumor regression scores (TRS) were assessed in 236 rectal cancer patients who treated with nCRT followed by surgery. Survival analysis was performed using Cox proportional hazards models. Results: Among these patients, the stage of 88 patients was ypII, and 91 patients were with the stage of ypIII. The median follow-up time was 59.8 months. TRS was not an independent prognostic factor in ypII patients while it was significantly associated with the prognosis of ypIII patients (5-year survival rate 67.2% vs. 42.5%, P < 0.001). Furthermore, ypIII patients with the response to nCRT had similar survival to that of ypII patients (5-year survival rate 67.2% vs. 70.5%, P = 0.56). For ypIII patients, multivariable analysis showed that well differentiation, negative surgical margin, and the administration of adjuvant chemotherapy were associated with better survival. The surgical margin and differentiation were prognostic factors for ypII patients. Conclusions: ypIII rectal cancer patients with poor response to preoperative treatment are at high risk of worse oncological outcomes.